2013
DOI: 10.1155/2013/493643
|View full text |Cite
|
Sign up to set email alerts
|

Mood and Memory Function in Ovariectomised Rats Exposed to Social Instability Stress

Abstract: This study aims to compare the effects of social instability stress on memory and anxiety- and depressive-like behaviour between sham-operated controls and ovariectomised (OVX) rats. Forty adult female Sprague-Dawley rats (8 weeks old) were randomly divided into four groups, (n = 10 per group). These were non-stressed sham-operated control rats, stressed sham-operated control rats, non-stressed OVX rats, and stressed OVX rats. The rats were subjected to social instability stress procedure for 15 days. Novel ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 75 publications
1
8
1
1
Order By: Relevance
“…Increases in levels of corticosterone in stressed animals have been seen following other studies using physical stress (Al‐Rahbi et al., 2014), and higher levels of corticosterone were shown to be importantly involved in the negative effect on the animal's subsequent learning and memory and effects were concentration‐dependent (Kovács et al., 1976), suggesting in ovariectomized female rats, corticosterone levels could play a role in learning and memory deficits. In our study, sham‐operated rats did not exhibit a rise in corticosterone upon stressor exposure, which is in contrast to findings that physical stress for two weeks increased blood corticosterone levels in ovarian intact animals, which could be due to differences in duration of the stress, the type of stress, the breed of the animal, or/and the age of the animal between the two studies (Al‐Rahbi et al., 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Increases in levels of corticosterone in stressed animals have been seen following other studies using physical stress (Al‐Rahbi et al., 2014), and higher levels of corticosterone were shown to be importantly involved in the negative effect on the animal's subsequent learning and memory and effects were concentration‐dependent (Kovács et al., 1976), suggesting in ovariectomized female rats, corticosterone levels could play a role in learning and memory deficits. In our study, sham‐operated rats did not exhibit a rise in corticosterone upon stressor exposure, which is in contrast to findings that physical stress for two weeks increased blood corticosterone levels in ovarian intact animals, which could be due to differences in duration of the stress, the type of stress, the breed of the animal, or/and the age of the animal between the two studies (Al‐Rahbi et al., 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, modulation of the GR response by ERβ‐mediated signaling can be induced in this nucleus, as ERβ agonists reduced stress‐induced anxiety‐type behaviors and eliminated CORT secretion upon a stressor in the central nucleus of the amygdala (Weiser et al., 2010). In ovariectomized animals which exhibited higher levels of anxiety due to psychological stress compared with sham animals, estrogen attenuated release of CRF, and modulated HPA axis activity through ERβ in the paraventricular nucleus (Al‐Rahbi et al., 2013). One proposed mechanism for estrogen‐mediated reductions in stress‐induced anxiety in overiectamized rats is that ERβ signaling in amygdala reestablishes equilibrium between GABAergic and glutamatergic transmission in the basolateral amygdala through alterations in inhibitory and excitatory receptor up and downregulation (Tian et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this spontaneous behaviour was not observed in SD rats, which were shown to be more vulnerable to isolation-induced anxiety and depressive-like behaviours (Weiss et al ., 2000 ). Additionally, anxiety- and depressive-like behaviour were significantly increased in social instability stressed SD females compared to non-stressed ovariectomised rats yet not in sham-operated controls, suggesting a protective role of sex hormones in the development of stress-induced behavioural disorders in females (Al-Rahbi et al ., 2013 ). Thus the effect of stress on open field behaviour depends on many factors and variable results can be observed depending on protocol, strain, sex and age of the subjects tested.…”
Section: Open Field Test: Equipment and Procedures Of Testingmentioning
confidence: 99%
“…Stress and oestrogen (E2) deficiency are the major contributors in increasing an individual's susceptibility to oxidative stress and affective disorders. Recently, our research group reported increased anxiety-like behavior in stressed ovariectomized (OVX) rats compared with nonstressed OVX or stressed sham-operated controls [ 14 ]. It was suggested that high circulating corticosterone acts synergistically with low circulating E2 to exert negative effects on the mood.…”
Section: Introductionmentioning
confidence: 99%